PENGARUH AROMATERAPI LAVENDER (Lavandula Angustifolia) TERHADAP PENGURANGAN MUAL MUNTAH IBU HAMIL TRIMESTER I - Okti Satria; Yohana Suganda; Wira Meiriza; Rika Armalini (Jurnal Kesehatan Medika Saintika, 2025)
Nausea and vomiting are common conditions experienced by pregnant women, which can interfere with the quality of life and the health of both the mother and the fetus. This study aims to analyze the effect of lavender aromatherapy on the reduction of nausea and vomiting in pregnant women during the first trimester (TM I) at PMB Hj. STr. Keb Yetti Latief in 2024. In this study, lavender aromatherapy intervention was applied to a group of pregnant women experiencing nausea and vomiting symptoms, with measurement of symptom intensity before and after the intervention. The method used was a comparative test between the group before receiving lavender aromatherapy and the group after receiving the treatment. The study was conducted at PMB Hj. Yetti Latief, STr. Keb, from September 6-20, 2024. The results showed a significant decrease in nausea and vomiting frequency and intensity in the group that received lavender aromatherapy, with a p-value of 0.001 < 0.005. This indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, meaning there is a significant effect of lavender aromatherapy on reducing nausea and vomiting intensity in pregnant women. This shows that lavender aromatherapy can be an effective non-pharmacological alternative in managing nausea and vomiting during pregnancy. It is hoped that this study can contribute to the development of non-pharmacological therapies for nausea and vomiting during pregnancy, as well as increase understanding of the benefits of lavender aromatherapy in maternal health care.